Decentralized improvement on floor control mechanism for PoC - Hai-peng LIU; Jian-xin LIAO; Xiao-min ZHU (Tongxin xuebao)
TBCP(talk burst control protocol)has been defined as the floor control mechanism for PoC(push to talk over cellular)service by OMA(open mobile alliance).It is a centralized controlling mechanism which has several limitations as other central approaches have,such as bottleneck effect,bad scalability,high maintenance cost of the central node,etc.In order to overcome the deficiencies of TBCP,two novel distributed floor control mechanisms were put forward,TBCP/DQ(distributed queue) and TBCP/MQ(mobile queue).After analytical and experimental evaluations,the new approaches serve well for PoC and even all CMA(collaborative multimedia application)services.